A Novel Strategy for Carbon Capture and Sequestration by rHLPD Processing - Li, Qinghua; Gupta, Surojit; Tang, Ling; Quinn, Sean; Atakan, Vahit; Riman, Richard E. (Frontiers in Energy Research, 2016)
Monoethanolamine (MEA) scrubbing is an energy intensive process for Carbon Capture and Sequestration (CCS) due to the regeneration of amine in stripping towers at high temperature (100-120 ºC) and the subsequent pressurization of CO2 for geologic sequestration. In this paper, we introduce a novel method, reactive hydrothermal liquid phase densification (rHLPD), which is able to solidify (densify) monolithic materials without using high temperature kilns. Then we integrate MEA-based CCS processing and mineral carbonation by using rHLPD technology. This integration is designated as rHLPD-Carbon Sequestration (rHLPD-CS) process. Our results show that the CO2 captured in the MEA-CO2 solution was sequestered by the mineral (wollastonite CaSiO3) carbonation at a low operating temperature (60 ºC) and simultaneously monolithic materials with a compressive strength of 121 MPa were formed. This suggests that the use of rHLPD-CS technology eliminates the energy consumed for CO2-MEA stripping and CO2 compression and also sequesters CO2 to form value-added products, which have a potential to be utilized as construction and infrastructure materials. In contrast to the high energy requirements and excessive greenhouse gas emissions from conventional Portland cement manufacturing, our calculations show that the integration of rHLPD and CS technologies provides a low energy alternative to production of traditional cementitious binding materials.